Hypothalamic POMC Deficiency Improves Glucose Tolerance Despite Insulin Resistance by Increasing Glycosuria - Chhabra, Kavaljit H. (2016)
Hypothalamic proopiomelanocortin (POMC) is essential for the physiological regulation of energy balance; however, its role in glucose homeostasis remains less clear. We show that hypothalamic arcuate nucleus (Arc)POMC-deficient mice, which develop severe obesity and insulin resistance, unexpectedly exhibit improved glucose tolerance and remain protected from hyperglycemia. To explain these paradoxical phenotypes, we hypothesized that an insulin-independent pathway is responsible for the enhanced glucose tolerance. Indeed, the mutant mice demonstrated increased glucose effectiveness and exaggerated glycosuria relative to wild-type littermate controls at comparable blood glucose concentrations. Central administration of the melanocortin receptor agonist melanotan II in mutant mice reversed alterations in glucose tolerance and glycosuria, whereas, conversely, administration of the antagonist Agouti-related peptide (Agrp) to wild-type mice enhanced glucose tolerance. The glycosuria of ArcPOMC-deficient mice was due to decreased levels of renal GLUT 2 (rGLUT2) but not sodium–glucose cotransporter 2 and was associated with reduced renal catecholamine content. Epinephrine treatment abolished the genotype differences in glucose tolerance and rGLUT2 levels, suggesting that reduced renal sympathetic nervous system (SNS) activity is the underlying mechanism for the observed glycosuria and improved glucose tolerance in ArcPOMC-deficient mice. Therefore, the ArcPOMC-SNS-rGLUT2 axis is potentially an insulin-independent therapeutic target to control diabetes